Functional Patterning of Biopolymer Thin Films Using Enzymes and Lithographic Methods. (28th August 2012) - Kargl, Rupert; Mohan, Tamilselvan; Köstler, Stefan; Spirk, Stefan; Doliška, Aleš; Stana‐Kleinschek, Karin; Ribitsch, Volker
Abstract Two different lithographic techniques for the patterning of thin biopolymer films are developed. The first method is based on using a microstructured elastomeric mold for the structuring of thin films of regenerated cellulose. The thin films are manufactured by spin‐coating of trimethylsilyl cellulose (TMSC) and subsequent regeneration. The microchannels formed by the mold and the cellulose film are filled with a cellulase solution by capillary action. In the areas exposed to the enzyme solution, the cellulose film is digested, whereas the area in contact with the mold is protected from the enzymatic activity. Optical thickness measurements, atomic force microscopy and fluorescent staining confirm a successful patterning of cellulose on several substrates by this method. The second method is based on the structured regeneration of thin TMSC films. TMSC surfaces are protected with metal masks and exposed to vapors of hydrochloric acid. These treatments result in hydrophilic cellulose structures surrounded by hydrophobic TMSC with differing physicochemical properties. Treatments of the obtained structures with cellulases allow the selective removal of pure cellulose, whereas a TMSC pattern remains on the surface. These TMSC can be regenerated back to pure cellulose by treatments with vapors of hydrochloric acid. The developed methods allow the effective fabrication of micropatterned biopolymer thin films suitable for further functionalization and application in, e.g., bioanalytical devices. This is shown by the immobilization and detection of single‐stranded DNA on structured cellulose surfaces. Owing to the versatility of both patterning approaches the methods can be further extended to other combinations of substrates and enzymes.